(untitled) (Journal of Business, Universidad del Pacífico (Lima, Peru), 2017)
This article presents a theoretical equation set based on the information interactions that result in experiential learning. We attempt to link our equation set to the Uppsala Internationalization Process model in order to quantify information overload and operationalize the Uppsala model under longitudinal time series settings. The internationalization process has generated an increase in the diversity and overall quantity of information, resulting in an increase of the variation and amount of information that a firm needs to process. This challenges a firm’s capacity to simultaneously expand and learn. Market knowledge is acquired essentially through current business activities, all of which proceed from a firm’s market experience to generate experiential knowledge. Market experience is situation-specific and therefore difficult to generalize. Nonetheless, firms tend to use general “failsafe proven courses of action” when confronted with new situations in an effort to reduce diverging, larger quantities of incoming and often discrepant information. Information overload refers to situations where the quantity of information pending analysis and consideration compels a firm to revert to older and trusted information processing methods instead of seeking adaptive solutions, clearly adopting a short-term efficiency posture leading to suboptimal performance.